Numbers of early career psychiatrists vary markedly among European countries - Nawka, Alexander; Kuzman, Martina Rojnic; Giacco, Domenico; Pantovic, Maja; Volpe, Umberto (Psychiatria Danubina, 2015)
In the field of psychiatry the decline of recruitment and brain-drain are currently one of the most discussed topics among stakeholders on national and European level. Even though comprehensive data on psychiatric training in Europe have been already reported, no data are available on even the approximate number of early career psychiatrists (ECPs). With this objective in mind, the Early Career Psychiatrists Committee of the European Psychiatric Association (EPAECPC) and the European Federation of Psychiatric Trainees (EFPT) have undertaken a survey. Based on the methodology used, the total number of ECPs in all European countries was 46 144 with the average number of ECPs being 5.5/100 000 country inhabitants. The actual numbers in this respect varied greatly among countries from 0.4 and 0.6 ECPs/100 000 in Azerbaijan resp. Russia; to 20.4 and 28.4 ECPs/100 000 in Norway resp. Switzerland. An obvious East-West gradient with increasing numbers of ECPs when moving from East to West, and from South to North were found, mirroring the economic strength of European countries. This is the first study to specifically explore the number of ECPs across Europe which might have key implications for planning and establishing recruitment activities and for developing strategies for prevention of brain-drain, such as improvement of educational system and enlargement of professional opportunities.
Keywords: psychiatrie; Psychiatry; lidé; Evropa; Humans; Europe